Radioactive Safety Assessment for Surface Contamination by using SAFRAN Tool - Mezher Abed Gatea; Saad Jundee Kadhum (Journal of Madenat Alelem University College, 2019)
This research presents the deterministic safety assessment for work activities carried out to remediate the surface radioactive contamination which found during the decommissioning of Radioisotopes Production Laboratory (RPL) at Al-tuwiatha nuclear site, to demonstrate that the dose acceptance criteria and the safety goals are met with a high degree of confidence. Work activities comprised characterizing, removal, packaging and relocating of the generated waste into specified zone. The physical status of the affected area is soil and debris and radiologically contaminated with (Cs-137, Eu-152, Co-60) and small amounts of natural Uranium. Safety assessment calculations have done by using SAFRAN (Safety Assessment Framework) version 2.3.2.7 software. The radiation exposure for workers in the affected area is considered as an endpoint to be compared to the worker dose limit. Dose to the public is considered to be negligible and is not numerically assessed in the SAFRAN file due to that RPL is located in a restricted zone far away from the public, low level radioactivity for the affected area and 30m berm surrounded Al-tuwiatha site. Assessment for accident conditions, were also considered to be negligible because no accident occurs in all activities of work. Safety assessment calculations based on maximum external dose rate (2.233µSv/h) and maximum air contamination (0.001Bq/m3). Safety assessment results proved that the sum of external and internal doses to the workers for all work activities were 1.6mSv/y is less than 10% of the 20mSv/y dose limit. Hence, there are no activities that have been assessed to present a risk rating higher than low and the radiological risks remain below the relevant prescribed dose limits through implementing effective safety programs into remediation process of the surface contamination.